Three-dimensional ultrasound evaluation of the pelvic floor in postmenopausal women using hormone therapy - Marques Gomes Delmanto, Lucia Regina [UNESP]; Omodei, Michelle Sako [UNESP]; Bueloni-Dias, Flavia [UNESP]; Pontes, Ana Gabriela [UNESP]; Delmanto, Armando [UNESP]; Spadoto-Dias, Daniel [UNESP]; Nahas, Eliana Aguiar Petri [UNESP] (Elsevier, 2021)
OBJECTIVE: To evaluate the three-dimensional (3D) ultrasound characteristics of the pelvic floor muscles (PFM) in two groups of postmenopausal women: users and nonusers of menopausal hormone therapy (MHT). STUDY DESIGN: Observational, cross-sectional cohort study. MAIN OUTCOME MEASURES: In this study 226 sexually active heterosexual women, aged 45-60 years with amenorrhea >12 months and without clinical pelvic floor disorders or urinary incontinence were included. Women using MHT ≥ 6 months were classified as systemic users. PFM strength was assessed by digital vaginal palpation and scored on the Modified Oxford Scale. Biometry of the PFM was performed by 3D transperineal ultrasound for evaluation of total urogenital hiatus area, transverse and anteroposterior diameters, and levator ani muscle thickness. RESULTS: The participants were divided into users (n = 78) and nonusers (n = 148) of MHT. There were no differences in clinical or anthropometric parameters between groups. The mean age was 55 years and the time since menopause was six years in both groups. The mean duration of MHT use was 43.4 ± 33.3 months. Users of MHT had greater levator ani muscle thickness (p = 0.001) and higher PFM strength (p = 0.029) than nonusers. Risk analysis adjusted for age, time since menopause, BMI, parity, and type of delivery showed an association of MHT use with greater levator ani muscle thickness (OR = 2.69; 95% CI 1.42-5.11, p = 0.029), and higher PFM strength (OR = 1.78; 95% CI1.01-3.29, p = 0.046). There was a weak positive correlation between levator ani muscle thickness and duration of MHT use (r = 0.25, p = 0.0002) and PFM strength (r = 0.12, p = 0.043). CONCLUSIONS: Postmenopausal women using MHT had a greater levator ani muscle thickness associated with higher PFM strength than nonusers.
Keywords: Menopausal hormone therapy; Menopause; Pelvic floor; Three-dimensional ultrasound